Analisis Strategi Pemasaran Islam untuk Meningkatkan Jumlah Penjualan Produksi Siwalan di Banaresep Timur Kecamatan Lenteng - sinta waliyah11 masyhurat (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
This study seeks to answer the question of the Islamic marketing strategy used by the people of East Banaresep to increase the number of sales of siwalan production. And why can the Siwalan marketing strategy in East Banaresep not be confirmed as a life support? This research is also used to understand how are the stages of marketing productively to improve people's mindsets in developing the production of siwalan? This study uses a qualitative method to explore Islamic marketing strategies in increasing the number of siwalan production in East Banaresep Village. In the process of collecting the researchers using observation, interview, documentation, triangulation, and data presentation techniques, drawing conclusions using SWOT analysis. This study shows that productive processing can increase the purchasing power of the wider community. The results of this study are, the marketing area of ​​the selected product for the siwalan seller in the East Banaresep area and its surroundings. This is due to the limited capital owned by the siwalan home industry. the marketing strategy carried out by the siwalan home industry is only with personal closeness and sales around the roadside. The lack of understanding and management skills in terms of digital or e-commerce has made owners not optimally utilize existing media. Based on the SWOT analysis conducted on the Siwalan marketing, several strategies have been formulated in an effort to increase selling power, including the following: Maintaining price and product quality to increase consumer loyalty; Establish mutually beneficial cooperation to expand the marketing area; Increase the amount of production ahead of the dry season, Maintain product quality, change packaging design to make it more attractive to consumers, Utilize technological developments as a means of promotion, Increase business capital to expand marketing areas and increase production, Expand marketing areas and conduct promotions to attract consumers.